Prediction of the performance of a solar water detoxification system under Malaysian climatic conditions - Jubran, B.A. (Pergamon, 2000)
This paper reports a prediction study for computing the ultra violet (UV) light received by two types of solar collector systems used in solar detoxification systems under Malaysian climatic conditions. Furthermore, the average daily yield outputs of two types of solar detoxification are predicted. The predicted results indicate that the average daily UV light insolation throughout the year in Malaysia is almost constant with values of 40 and 30 W/m2 for flat plate and compound parabolic concentrator (CPC) collectors, respectively. The average daily yield outputs of the solar detoxification systems investigated are 1000 l/m2 for the flat plate collector and 600 l/m2 for the CPC collector with unit costs per 1000 gallons of $36 and $42 for flat plate and CPC collectors, respectively.